The Occurrence and Survival of the Soul in Terms of the Philosophers (Aristotle and Ibn Sina) - AYAD NAEEM MAJEED ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2023)
This study dealt with the occurrence and survival of the soul, to show the ramifications of this topic and its partial details with rational pieces of evidence according to the opinions of the wise: Aristotle and Ibn Sina. The pieces of evidence include: proving the existence of the soul, defining it, stating its essentiality, proving its unity with proving the existence of its multiple powers, proving its abstraction, its occurrence, and its association with the body, and its connection with the active mind. The study proved with the rational evidence followed by Aristotle and Ibn Sina that the soul is an accident, it was not ancient, and it will remain without the occurrence of the suspicion of reincarnation after the separation of the bodies. However, this survival after the annihilation of the body, according to the opinion of the wise Aristotle, does not apply to the completeness of the soul, but only to what concerns the mind. Because complete self cannot be achieved by it. While the wise Ibn Sina believes that the origin of man is the soul that does not accept dissolution or non-existence after the demise of the body, and its fate is not dependent on the fate of the body. And when the body is corrupted or perishes due to any of the reasons, the soul remains immortal, preserving its existence in the other world.